Disclosure of the integrity of the Algerian banking system through the analysis of macroeconomic indicators for the period (2006/2019) - Tardkhodja, Hichame (Finance and Business Economies Review, 2022)
This study aims to reveal the integrity of the banking system through the analysis of macroeconomic indicators, which is included in the quantitative indicators of total prudence, which is one of the most important components of the early warning system for banking crises, in addition to the method of structural control represented in the indicators of partial prudence in addition to the standard of analysis of current expenditures and revenues. And the international rules of caution represented by the Basel Accords. The study reached a set of results, most notably that the process of tracking macroeconomic indicators is of paramount importance, as they are often a main source of crises. The study also concluded that the Algerian banking system cannot be exposed to a crisis, at least in the short term.